Alternative models of input - output for the evaluation of relative performance for a Greek bank's network of branches - Δονάτος, Γεώργιος Σ.; Γκιώκας, Δημήτριος; Αθανασόπουλος, Ανδρέας (SPOUDAI Journal of Economics and Business, 2002)
This paper presents a systematic application of Data Envelopment Analysis in estimating the relative efficiency of the branches of a Greek Bank. Three different main approaches were used according to the choice of how to measure the flow of services (outputs) provided by Bank branches. The three approaches were compared by applying all to the same data set of bank branches. Little differences were found in the distribution of efficiency estimates. Overall, this comparative study reveals that inferences regarding efficiency may be affected by how output is measured. JEL Classification: C61, M1l